Identification of WRKY gene family members in amaranth based on a transcriptome database and functional analysis of AtrWRKY42-2 in betalain metabolism - Yang, Rongzhi; Huang, Tianliu; Song, Weiwei; An, Zixian; Lai, Zhongxiong; Liu, Shengcai (Frontiers in Plant Science, 2023)
WRKY TFs (WRKY transcription factors) contribute to the synthesis of secondary metabolites in plants. Betalains are natural pigments that do not coexist with anthocyanins within the same plant. Amaranthus tricolor ('Suxian No.1') is an important leaf vegetable rich in betalains. However, the WRKY family members in amaranth and their roles in betalain synthesis and metabolism are still unclear. To elucidate the molecular characteristics of the amaranth WRKY gene family and its role in betalain synthesis, WRKY gene family members were screened and identified using amaranth transcriptome data, and their physicochemical properties, conserved domains, phylogenetic relationships, and conserved motifs were analyzed using bioinformatics methods. In total, 72 WRKY family members were identified from the amaranth transcriptome. Three WRKY genes involved in betalain synthesis were screened in the phylogenetic analysis of WRKY TFs. RT-qPCR showed that the expression levels of these three genes in red amaranth 'Suxian No.1' were higher than those in green amaranth 'Suxian No.2' and also showed that the expression level of AtrWRKY42 gene short-spliced transcript AtrWRKY42-2 in Amaranth 'Suxian No.1' was higher than that of the complete sequence AtrWRKY42-1, so the short-spliced transcript AtrWRKY42-2 was mainly present expressed in 'Suxian No.2' amaranth.Moreover, the total expression levels of AtrWRKY42-1 and AtrWRKY42-2 were down-regulated after GA 3 treatment, so AtrWRKY42-2 was identified as a candidate gene.Therefore, the short splice variant AtrWRKY42-2 cDNA sequence, gDNA sequence, and promoter sequence of AtrWRKY42 were cloned, and the PRI 101-AN-AtrWRKY42-2-EGFP vector was constructed to evaluate subcellular localization, revealing that AtrWRKY42-2 is located in the nucleus. The overexpression vector pRI 101-AN-AtrWRKY42-2-EGFP and VIGS (virus-induced gene silencing) vector pTRV2-AtrWRKY42-2 were transferred into leaves of 'Suxian No.1' by an Agrobacterium-mediated method. The results showed that AtrWRKY42-2 overexpression could promote the expression of AtrCYP76AD1 and increase betalain synthesis. A yeast one-hybrid assay demonstrated that AtrWRKY42-2 could bind to the AtrCYP76AD1 promoter to regulate betalain synthesis. This study lays a foundation for further exploring the function of AtrWRKY42-2 in betalain metabolism.